Transareolar uniportal thoracoscopic extended thymectomy for patients with myasthenia gravis - Lin, Jianbo; Lin, Nanlong; Li, Xu; Lai, Fancai (Frontiers in Surgery, 2022)
Background: Transareolar uniportal thoracoscopic extended thymectomy (TUTET) has not been previously reported. We attempted to assess the feasibility and safety of TUTET for male myasthenia gravis (MG) patients. Patients and methods: From February 2013 to February 2020, 46 men with MG underwent TUTET. All patients were followed up for 12 to 84 months postoperatively by clinic visits or telephone/e-mail interviews. Results: All surgeries were completed successfully, with an average operation time of 72.6 minutes. The mean length of transareolar uniportal incision was 3.0 ± 0.4 cm, and the mean postoperative cosmetic score was 3.1 ± 0.5 at discharge. Three months postoperatively, no patients had an apparent surgical scar on the chest wall or complained of postoperative pain. Substantial amelioration of the disease was achieved in a short period, and several benefits were clear. At the 1-year follow-up, all patients showed a good cosmetic effect and high satisfaction. Conclusions: TUTET is an effective and safe way for men with MG. The uniportal incision is hidden in the areola with sound cosmetic effects. We believe that TUTET is an acceptable procedure for extended thymectomy.